Succession of the image of the city in the movement for urban design by local proprietors in Ginza from pre-war to post-war - Miyashita, Takahiro; Nakajima, Naoto (International Planning History Society Proceedings, 2018)
This paper revealed the development of the movement for urban design by local proprietors in Ginza, Tokyo from 1930’s to 1960’s. Ginza Street is known as one of the first modern style streets in Japan. This street has developed greatly by modern buildings and advanced urban design methods in modern times and after although it has also suffered serious damage twice by Great Kanto Earthquake (1923) and bombing in 1945. Therefore, buildings and urban space have seen repeated reconstruction and renewal until today. On the other hand, if we pay attention to local proprietors, we can understand that they have developed the movement for urban design of Ginza Street continuously and succeeded the awareness of the issues toward urban space. So this paper finds a new historical context of Ginza through the elucidation of development of their movement from viewpoints of how the awareness of the issues and the image of spaces have changed.